R. v. Spencer: Anonymity, the Rule of Law, and the Shrivelling of the Biographical Core - Hunt, Chris; Rankin, Micah (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
The Supreme Court of Canada’s recent decision in R. v. Spencer is likely to become a landmark decision on informational privacy. Spencer addressed the issue of whether an Internet user charged with possession and distribution of child pornography had a Charter-protected privacy interest in his Internet subscriber information. A unanimous Supreme Court answered this question in the affirmative, primarily because such information could lead to the identification of a user carrying out intimate or sensitive activities in circumstances where the user would believe that his or her activities would be carried out anonymously. The immediate practical consequence of Spencer is that police will henceforth be required to obtain prior judicial authorization before requesting a person’s Internet subscriber information—a holding that squarely contradicts a number of recent appellate court decisions. In this comment, the authors argue that Spencer is likely to have a significant, and possibly transformative, impact on section 8 jurisprudence. In their view, the Court’s recognition of “anonymity” as an independent value underlying section 8 of the Charter leads to a more robust account of privacy—an account that is more consistent with theoretical approaches to the concept. The authors argue that the recognition of a right to anonymity may also serve to support the rule of law by refocusing the section 8 analysis on unwanted scrutiny by the state. In addition, an emphasis on the right to anonymity may lead to a diminished role for the analytical device known as the “biographical core”. The authors conclude their comment with a discussion of the Court’s decision to admit the impugned evidence under section 24(2) of the Charter, arguing that the Court placed too much emphasis on the legal uncertainty surrounding the search.